Intelligence Law Enforcement and Intelligence Strategy in Forex Robot Development in Indonesia - Alam, Seala Syah; Runturambi, A Josias Simon (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
In the development of technology in the financial world, we are also now familiar with trading robots. This robot serves to facilitate trading in cyberspace. Trading robots do not offer a solution to generate profitable transactions instantly. Profitable long-term forex trading is more than just tactical analysis of forex trading and the use of trading robots. Have a special program that does all the work to make it look tempting. But this is how trading robots work. Trading robot sellers who prefer to see a decent trading robot. Such a system requires constant human adaptation and supervision. The general public who wants to use trading robots properly must know the risks and systems of trading robots and there is no guarantee that using a trading robot will be 100% profitable. It should be reiterated that the trading robot will make decisions based on the conditions that have occurred and the right decisions at that time. Thus, no foreign trade organizer dares to give absolute guarantees.